METHOD FOR CONTROLLING PORE DIAMETER OF COLLODION MEMBRANE AND METHOD FOR PRODUCING FUNCTIONAL POLYMER MEMBRANE - OKUDA NAOYA; KANDA MOMOKO; KAWANO KOSUKE; KAIZUMI TOSHINARI; TAKAHASHI SHINICHIRO; ONAKA TATSURO; ERA IORI; KUMAGAI RURI; KONDO HIROSHI; NOUCHI KOSUKE; SHIBATA SHINJI; NISHIMOTO YUSUKE; et al. (2013)
PROBLEM TO BE SOLVED: To control pore diameters of separation/filtration membrane in accordance with the size of subject matter to be separated by freely controlling the pore diameters in the same polymer membrane, and further to provide a production method of a functional polymer membrane by confining a low molecule having functionality within a polymer membrane by means of the control method of pore diameter.SOLUTION: The control method of enlarging pore diameters comprises adding water molecules in an ethanol solution state and forming a membrane when forming the collodion membrane, and thereafter removing the water molecules. The control method of contracting pore diameters comprises adding salicylic acid and forming a membrane when forming the collodion membrane. The production method of the functional polymer membrane comprises adding salicylic acid and cobalt chloride when forming the collodion membrane to confine the cobalt chloride within pores of the collodion membrane by using the control method of contracting pore diameters. Herewith, the functional polymer membrane is obtained by confining cobalt chloride within the pore having new pore diameters of the collodion membrane composed of high molecular pyroxylin and salicylic acid.